Reframing islamic identity: The role of arabic vocabulary interpretation materials in islamic education for the digital era in multicultural society - Fadhilah; Syabuddin Gade; Ainal Mardhiah; Teuku Zulfikar (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The rapid expansion of digital technologies has fundamentally reconfigured the production, circulation, and interpretation of Islamic knowledge, creating profound challenges for the construction of Islamic identity in increasingly multicultural societies. Despite growing scholarly attention to digital religion and Islamic education, existing studies remain fragmented and have yet to offer an integrative framework that explains how interpretive processes shape identity formation. This study addresses this gap by examining how Qur’anic vocabulary interpretation can function as a strategic pedagogical mechanism for reframing Islamic identity in the digital era. Employing a qualitative theory-building approach, the study synthesizes insights from 65 scholarly sources, including peer-reviewed journal articles and academic books, to develop a comprehensive conceptual model. The analysis focuses on key Qur’anic concepts such as ‘adl (justice), rahmah (compassion), and ummah (community), exploring their transformation within digitally mediated and culturally diverse learning environments. The findings reveal that digital platforms shift interpretive authority from hierarchical structures to participatory ecosystems, enabling learners to actively construct meaning while simultaneously exposing them to fragmented and decontextualized interpretations. This dual dynamic generates a critical paradox in which increased accessibility often undermines interpretive depth and coherence. In response, this study proposes the “Mufradat Connect” model, an integrative framework that combines layered interpretation, digital engagement, and intercultural dialogue. The study contributes theoretically by advancing a vocabulary-centered paradigm that bridges Islamic education, digital religion, and identity studies, and practically by offering a structured approach for designing contextually responsive learning environments. Ultimately, it redefines Islamic identity as a dynamic, reflective, and contextually grounded construct capable of navigating the complexities of the contemporary global landscape.